Prognostic impact of MitraClip in patients with left ventricular dysfunction and functional mitral valve regurgitation: A comprehensive meta-analysis of RCTs and adjusted observational studies. (1st September 2019) - Bertaina, Maurizio; Galluzzo, Alessandro; D'Ascenzo, Fabrizio; Conrotto, Federico; Grosso Marra, Walter; Frea, Simone; Alunni, Gianluca; Crimi, Gabriele; Moretti, Claudio; Montefusco, Antonio; D'Amico, Maurizio; Perl, Leor; et al.
Abstract: The real prognostic impact of MitraClip in patients with significant functional mitral regurgitation (FMR) and left ventricular (LV) dysfunction remains to be elucidated. Two randomized controlled trials (RCTs) with conflicting results have been recently published. We conducted a comprehensive meta-analysis of all RCTs and adjusted observational studies to evaluate the clinical impact of percutaneous mitral valve repair when compared with optimal medical therapy (OMT) alone, in patients with symptomatic FMR and LV dysfunction. Death from any cause and heart failure rehospitalizations at the longest available follow-up were the primary endpoints. Cardiac death, one year and short-term death were the secondary ones. 2255 patients (1207 for MitraClip and 1048 for OMT-only) from 8 studies (2 RCTs and 6 observational studies) were included. At a median (mid-term) follow-up of 438 days (IQR 360–625) MitraClip was associated with a significant reduction of all-cause death (odds Ratio [OR] 0.55, 95%CI 0.41–0.73, p < 0.001; [ORadj] 0.66, 95%CI 0.49–0.90, p = 0.009) and rehospitalization (OR 0.49, 95%CI 0.24–1.00, p = 0.05 and ORadj 0.63, 95%CI 0.43–0.94, p = 0.02). At one year, adjusted analysis demonstrated a trend favoring the experimental cohort (ORadj 0.73, 95%CI 0.53–1.02, p = 0.07). Meta-regression suggested that benefit of MitraClip on mid-term survival persists even after accounting for the prevalence of implanted CRT, burden of comorbidities, NYHA class, cardiomyopathy etiology and LV function and dimensions. In conclusion, MitraClip for FMR in patients with LV dysfunction is associated with a considerable reduction of death and HF hospitalization at mid-term follow-up. Further ongoing RCTs are needed to strengthen present results. Highlights: MitraClip may reduce death and HF hospitalizations in functional mitral regurgitation. The reduction in death seems to emerge after the first year from Mitraclip. These benefits persist irrespective of age, CRT, functional class and comorbidities.